The Sociocultural Factors Underlying Latina Mothers' Infant Feeding Practices. (January 2019) - Cheney, Ann M.; Nieri, Tanya; Davis, Elizabeth; Prologo, Joe; Valencia, Esmirna; Anderson, Ashaunta T.; Widaman, Keith; Reaves, Christina; Sullivan, Greer
In this study, we examined the sociocultural factors underlying infant feeding practices. We conducted four focus groups with 19 Latina mothers of children 0 to 2 years of age enrolled in Early Head Start programs in the United States over a 1-year period. We found these mothers considered both science- and family-based feeding recommendations. However, advice from family was often inconsistent with science- and nutrition-based recommended feeding practices. In the interest of showing respect and preserving harmonious relationships, some mothers accepted family advice instead of recommended practices while others employed strategies to follow recommended practices without offending. Nutrition educators need to consider the intersection of macro, organizational, and community factors with micro-level processes in shaping the implementation of recommended feeding practices within family systems. Nutrition interventions for Latino families should capitalize on Latina mothers' strategies for navigating multiple information sources while preserving cultural values and family relationships.